KAJIAN PADA SISTEM PEMBIAYAAN MULTIJASA DI BMT NURUL UMMAH SUKABUMI - Syifa Nisrina (Nusantara Hasana Berdikari, 2021)
Multi-service financing is a business product from BMT to help the community's economy with the aim of making a profit. Multi-service financing uses an ijarah contract, namely a lease agreement, in this multi-service financing BMT is entitled to receive benefits in the form of ujrah/fee. Determining ujrah according to sharia rules must be expressed in nominal terms, currently in practice most are expressed in the form of proportions. Every financing must have risks and until now it is still an obstacle for BMT, a big challenge for BMT in order to be able to reduce these risks and not cause a large amount of financing which can ultimately result in large losses. Complex factors make BMTs have to build good risk management and help solve financing problems so they can continue to develop and contribute more to society through multi-service financing. This study aims to determine the multi-service financing system. The research method used is a qualitative method using primary data through interviews and several supporting documents. The results of this study indicate that the implementation of ijarah contracts in multi-service financing is not fully in accordance with sharia rules. Determining ujrah is appropriate but the use of benefits for services is not fully appropriate. Risk management and problem handling have not been going well and the level of collectibility is still high.